Insulator-to-metal transition in potassium-loaded zeolite P - Hettiarachchi, Gayan Prasad (Physical Society of Japan, 2015)
Potassium metal was loaded into porous crystals of potassium-form maximum aluminum zeolite P (K-MAP), and optical absorption, electrical resistivity, and magnetic susceptibility measurements were performed. The average loading density of potassium atoms per GIS cage of zeolite P, n, was systematically changed up to 1.09. Optical absorption bands are observed around 1.3-2 eV and grow to dominate the spectrum with increasing n. These absorption bands are assigned to the optical excitations of s-electrons confined in the zigzag channels of GIS cages. The temperature dependence of electrical resistivity ρ indicates insulating properties for n ≤ 1:05. At n = 1.09, ρ suddenly decreases by several orders of magnitude, and shows metallic properties indicating that an insulator-to-metal transition occurs between n = 1.05 and 1.09. The samples are basically nonmagnetic at any n. The nonmagnetic and insulating phase at n ≤ 1:05 is explained by the formation of small bipolarons in the spin-singlet states. The metallic phase at n = 1.09 is explained by the formation of large polarons